Ludological research traditions in the Institute of Applied Linguistics at Adam Mickiewicz University in Poznań - Surdyk, Augustyn (My University, 2011)
This paper aims to introduce briefly the basic assumptions of ludology as an academic discipline dealing with games research (including educational linguistic and communicational games in teaching foreign languages) and to present the achievements of the Games Research Association of Poland being the first ludological association in Poland, and closely cooperating with the Institute of Applied Linguistics at Adam Mickiewicz University in Poznań. The paper also summarises that cooperation and outlines the traditions of ludological research in glottodidactics and intercultural communication in the institute resulting in the recent foundation of the Center for Ludological Studies in Glottodidactics and Intercultural Communication and the foundation of the association's official journal "Homo Ludens".
Keywords: ludology; games research; applied linguistics; Polskie Towarzystwo Badania Gier; Games Research Association of Poland; Homo Ludens - the ludological journal